Mechanisms, genes and treatment: Experimental fear conditioning, the serotonin transporter gene, and the outcome of a highly standardized exposure-based fear treatment. (August 2018) - Wannemueller, André; Moser, Dirk; Kumsta, Robert; Jöhren, Hans-Peter; Adolph, Dirk; Margraf, Jürgen
Abstract: There is considerable interindividual variation in response to psychotherapeutical intervention. In order to realize the long-term goal of personalised treatment approaches, it is important to identify behavioural and biological moderators and mediators of treatment responses. Here, we tested the predictive value of experimental fear extinction efficacy as well as the role of genetic variation of the serotonin transporter gene for the outcome of a fear-exposure treatment. A discriminative fear conditioning paradigm was conducted in 159 adults highly fearful of spiders, dental surgeries or blood, injuries and injections. Participants were genotyped for the long (L) and short (S) allelic variant of the serotonin transporter gene linked polymorphic region (5HTTLPR) and treated with a highly standardized exposure-based one-session treatment. Participants' subjective fear was assessed during experimental fear conditioning and extinction. Furthermore, subjective phobic fear was assessed at pre-, post and at 7 months follow-up treatment assessment. A threat-biased contingency learning pattern characterized by exaggerated fear responses to the CS− was associated with larger initial subjective fear reduction immediately following the large-group treatment, p  = .03. There were no learning pattern-associated differences in subjective fear at 7-month follow-up. The odds of homozygous s-allele carriers to display a threat-biased contingency learning pattern were 3.85 times larger compared to l-allele carriers, p  = .01. Fear-recovery in homozygous S-allele carriers at follow-up assessment, p  = .01, emerged regardless of the experimental fear acquisition pattern. Our results suggest the homozygous S-allele carriers are biologically biased towards ignoring safety signals in threat-related situations. Short-term, this response pattern might be positively related to the outcome of exposure treatments, potentially due to increased responding to safe context conditions or a stronger violation of threat expectancies. However, alterations in inhibiting the response to cues formerly signalling threat evidenced for S-allele carriers can have negative impact on exposure success. Highlights: There is a need to identify mechanisms underlying the outcome of exposure treatments. We investigated the predictive value of fear conditioning and 5-HTTLPR genotype. Threat-biased contingency learning was associated with large post-treatment outcome. Homozygous S-allele carriers were more likely to show this pattern. We discuss possible underlying factors in relation to inhibitory learning.